Solar-assisted co-electrolysis of glycerol and water for concurrent production of formic acid and hydrogen. Issue 35 (28th July 2021) - Ke, Zunjian; Williams, Nicholas; Yan, Xingxu; Younan, Sabrina; He, Dong; Song, Xianyin; Pan, Xiaoqing; Xiao, Xiangheng; Gu, Jing
Abstract : A N-CoO x -catalyzed glycerol oxidation with a low energy supply (1.31 V) and high conversion of glycerol to formic acid (96.2% FE) was employed to repace OER and couple with solar-driven HER for co-production of formic acid and hydrogen. Abstract : Renewable electricity-driven water splitting provides a pathway to manufacturing hydrogen as a promising alternative to fossil fuels. A typical water electrolysis device is comprised of a cathodic hydrogen evolution reaction (HER) and an anodic oxygen evolution reaction (OER). Unfortunately, the OER consumes most of the overall electricity supply while generating negligible economic value, which inhibits the large-scale deployment of the water electrolysis technology. Here, we explored alternatives to the OER and demonstrated that electrooxidation of glycerol (a cheap byproduct of biodiesel and soap production) could lower anodic electricity consumption by up to 0.27 V while producing high-value formic acid with 96.2% faradaic efficiency (FE). Further, glycerol electrooxidation was combined with the photoelectrochemical HER to diminish the electricity requirement to 1.15 V, reducing the electricity consumption by ∼30% relative to typical water electrolysis. This study suggests that solar-assisted co-electrolysis of high-volume block chemicals and water may be an energy efficient and economically viable strategy to realize the sustainable production of value-added chemicals and hydrogen energy.